Surfactant-enhanced remediation of polycyclic aromatic hydrocarbons: A review - Lamichhane, S.; Bal Krishna, K.; Sarukkalige, Priyantha Ranjan (Academic Press, 2017)
Polycyclic aromatic hydrocarbons (PAHs) are toxic, mutagenic and carcinogenic organic compounds that are widely present in the environment. The bioremediation of PAHs is an economical and environmentally friendly remediation technique, but it is limited because PAHs have low water solubility and fewer bioavailable properties. The solubility and bioavailability of PAHs can be increased by using surfactants to reduce surface tension and interfacial tension; this method is called surfactant-enhanced remediation (SER). The SER of PAHs is influenced by many factors such as the type and concentration of surfactants, PAH hydrophobicity, temperature, pH, salinity, dissolved organic matter and microbial community. Furthermore, as mixed micelles have a synergistic effect on PAH solubilisation, selecting the optimum ratio of mixed surfactants leads to effective PAH remediation. Although the use of surfactants inhibits microbial activities in some cases, this could be avoided by choosing an optimum combination of surfactants and a proper microbial community for the targeted PAH(s), resulting in up to 99.99% PAH removal. This article reviews the literature on SER of PAHs, including surfactant types, the synergistic effect of mixed micelles on PAH removal, the impact of surfactants on the PAH biodegradation process, factors affecting the SER process, and the mechanisms of surfactant-enhanced solubilisation of PAHs.